Korelasi Antara Panjang Tangan dengan Tinggi Badan pada Suku Melayu Jambi - Nia Maimuria; Asan Petrus; Adriansyah Lubis (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Hand measurements are known to provide a good estimate of a person's height, which is particularly useful in the process of identifying human remains that are dismembered or separated due to various circumstances. Such conditions often occur during mass disasters, murders, airplane crashes, train collisions, and highway accidents. In forensic anthropology, hand length is one of the body measurements that can help estimate height when complete body parts are not available. This study aims to examine the relationship between hand length and height specifically in individuals from the Jambi Malay tribe, one of the ethnic groups in Indonesia. The research design used is analytic with a cross-sectional approach. The type of data used is primary data, obtained directly from 56 respondents belonging to the Jambi Malay tribe, both male and female. Statistical analysis showed that all independent variables — the length of the right and left hands, both in men and women, as well as without gender distinction — had a significant relationship with height. This is indicated by a P-value < 0.05 (P = 0.001). These results suggest that hand length can be a reliable predictor of height in this ethnic group. The study also highlights the importance of conducting further research involving other body parts and ethnic groups to support broader forensic identification efforts.